2014
DOI: 10.1152/ajpregu.00004.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary milk fat globule membrane improves endurance capacity in mice

Abstract: Milk fat globule membrane (MFGM) comprises carbohydrates, membrane-specific proteins, glycoproteins, phospholipids, and sphingolipids. We evaluated the effects of MFGM consumption over a 12-wk period on endurance capacity and energy metabolism in BALB/c mice. Long-term MFGM intake combined with regular exercise improved endurance capacity, as evidenced by swimming time until fatigue, in a dose-dependent manner. The effect of dietary MFGM plus exercise was accompanied by higher oxygen consumption and lower resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…Finally, the present study did not elucidate the active metabolites or underlying mechanisms for the beneficial effects of MFGM. Our previous study on mice suggested that sphingomyelin is one of the active components that accelerates neuromuscular development (13). Further investigation employing biochemical and detailed EMG analysis is necessary to clarify the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the present study did not elucidate the active metabolites or underlying mechanisms for the beneficial effects of MFGM. Our previous study on mice suggested that sphingomyelin is one of the active components that accelerates neuromuscular development (13). Further investigation employing biochemical and detailed EMG analysis is necessary to clarify the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies have demonstrated that dietary supplementation with MFGM, when combined with voluntary habitual exercise, improves both muscle mass and strength (12), and endurance capacity in mice (13). Our previous study revealed that the beneficial effects of dietary MFGM on skeletal muscles were associated with the stimulation of neuromuscular junction (NMJ) development, which is a critical structure of a motor unit.…”
mentioning
confidence: 99%
“…The soleus muscle is a prototypical slow-twitch muscle consisting primarily of Type I myofibres and thus a slow-to-fast fibre type shift could be seen to disrupt the normal profile of the soleus with the potential for possible negative effects on oxidative capacity. Nevertheless, Satoshi et al 2014 reported that mice receiving MFGM supplementation displayed increased muscular endurance capacity in association with increased soleus muscle mRNA expression of oxidative genes including peroxisome proliferator-activated receptor-γ coactivator 1α ( Pgc1α ) and Cpt-1b [50]. …”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with sphingomyelin combined with exercise increases the swimming time of mice and the level of peroxisome proliferator-activated receptor gamma coactivator 1α (PGC-1α) mRNA expression in the soleus muscle of mice. 15) It was shown in mice that sphingosine-1-phosphate, a product of sphingomyelin metabolism, promotes skeletal muscle regeneration. 16,17) In addition, sphingosine-1-phosphate stimulates the growth of human airway smooth muscle cells and increases in muscle contractile force in mice.…”
mentioning
confidence: 99%